2001
DOI: 10.1287/inte.31.1.30.9688
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Crew Scheduling at Air New Zealand

Abstract: The aircrew-scheduling problem consists of two important subproblems: the tours-of-duty planning problem to generate minimum-cost tours of duty (sequences of duty periods and rest periods) to cover all scheduled flights, and the rostering problem to assign tours of duty to individual crew members. Between 1986 and 1999, Air New Zealand staff and consultants in collaboration with the University of Auckland have developed eight application-specific optimization-based computer systems to solve all aspects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Many consulting companies are also offering products and services in this general area. Other testimonials on the impact of optimization in the airline industry can be found in Yu et al (2003), Butchers et al (2001), Wiper et al (1994, Smith et al (1992), and Patty et al (1991).…”
Section: Aircraft and Crew Schedule Planningmentioning
confidence: 99%
“…Many consulting companies are also offering products and services in this general area. Other testimonials on the impact of optimization in the airline industry can be found in Yu et al (2003), Butchers et al (2001), Wiper et al (1994, Smith et al (1992), and Patty et al (1991).…”
Section: Aircraft and Crew Schedule Planningmentioning
confidence: 99%
“…This impact is deeply significant when you consider that without revenue management and schedule-planning systems in the period 1990-2000, American Airlines would have been profitable in only one year, an all-time record year for profitability (Cook 2000). Other testimonials to the impact of optimization of the airline industry can be found in Yu et al (2003), Butchers et al (2001), Wiper et al (1994), Smith et al (1992), and Patty et al (1991).…”
Section: Introduction: Optimization and The Airline Industrymentioning
confidence: 99%
“…Nowadays, the rostering of pilots and cabin crew without such tools is unthinkable for all of the major airlines. In Butchers et al (2001), the authors estimate the annual savings of Air New Zealand to be around NZD 15 million, more than 6% of the annual estimated crew costs. Similarly, in Anbil et al (1991) annual savings in excess of USD 20 million are reported.…”
Section: Literature Reviewmentioning
confidence: 99%